Circulating the reverse flowing surplus power generated by single-phase DERs among the three phases of the distribution lines - Shahnia, Farhad; Ami, S.; Ghosh, Arindam (2016)
© 2015 Elsevier Ltd. Presence of large number of single-phase, customer-owned, distributed energy resources that are installed randomly in any phase of Low Voltage (LV) distribution feeders, may lead the generation, in a particular phase, to exceed its load demand. This may result in reverse power flow in that phase towards the upstream network while in the other phases, power flows from the upstream network to the LV feeder. To avoid such problems, this paper proposes the use of Distribution Static Compensators (DSTATCOM) to circulate the reverse flowing power from one phase to the other phases. In this paper, the installation of DSTATCOMs is considered in the medium voltage feeders. The DSTATCOM can be connected in either wye or delta, both of these connections are explored here. Different control strategies are developed for each connection. The main objective of the DSTATCOM is to provide a path for the power, to circulate among the phases, through its DC link. The DSTATCOM controller is further developed to balance its upstream powers and to supply the load reactive power demand. The proposed configurations and the developed control methods for the DSTATCOM are numerically validated through extensive computer simulation studies in PSCAD/EMTDC.